REALITA DIRI DALAM KARYA LUKIS - CANDRA DWI PUTRA, Yasrul Sami, S.Sn., M.Sn., Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2017)
This work aims to make the problem self as a container to visualize in the form of painting. The method in making this final work through several stages of preparation, elaboration, synthesis, concept realization, consultation with supervisor and completion lecturer. This work gives appreciation to the community of art lovers, especially painting, in order to try as much as possible to face problems and seek a good solution, even though it ends with undesirable conditionsKata Kunci: Realita diri, seni lukis, realis, kontemporer